Influence of different etching modes on bond strength to enamel using universal adhesive systems - Diniz, Ana C.S.; Bandeca, Matheus C.; Pinheiro, Larissa M.; Almeida, Lauber J dos Santosh; Torres, Carlos R.G. [UNESP]; Borges, Alvaro H.; Pinto, Shelon C.S.; Tonetto, Mateus R.; De Jesus Tavarez, Rudys R.; Firoozmand, Leily M. (Jaypee Brothers Medical Publishing, 2016)
Introduction: The adhesive systems and the techniques currently used are designed to provide a more effective adhesion with reduction of the protocol application. The objective of this study was to evaluate the bond strength of universal adhesive systems on enamel in different etching modes (self-etch and total etch). Materials and methods: The mesial and distal halves of 52 bovine incisors, healthy, freshly extracted, were used and divided into seven experimental groups (n = 13). The enamel was treated in accordance with the following experimental conditions: FUE-Universal System - Futurabond U (VOCO) with etching; FUWE - Futurabond U (VOCO) without etching; SB-Total Etch System - Single Bond 2 (3M); SBUE-Universal System - Single Bond Universal (3M ESPE) with etching; SBUWE - Single Bond Universal (3M ESPE) without etching; CLE-Self-etch System - Clearfil SE Bond (Kuraray) was applied with etching; CLWE - Clearfil SE Bond (Kuraray) without etching. The specimens were made using the composite spectrum TPH (Dentsply) and stored in distilled water (37 ± 1°C) for 1 month. The microshear test was performed using the universal testing machine EMIC DL 2000 with the crosshead speed of 0.5 mm/minute. The bond strength values were analyzed using statistical tests (Kruskal-Wallis test and Mann-Whitney test) with Bonferroni correction. Results: There was no statistically significant difference between groups (p < 0.05), where FUE (36.83 ± 4.9 MPa) showed the highest bond strength values and SBUWE (18.40 ± 2.2 MPa) showed the lowest bond strength values. The analysis of adhesive interface revealed that most failures occurred between the interface composite resin and adhesive. Conclusion: The universal adhesive system used in dental enamel varies according to the trademark, and the previous enamel etching for universal systems and the self-etch both induced greater bond strength values. Clinical significance: Selective enamel etching prior to the application of a universal adhesive system is a relevant strategy for better performance bonding.
Keywords: Acid etching; Adhesive systems; Shear strength